Pemodelan Ontologi Semantik: Padmasana Umat Hindu Bali - Wira Putra, I Gede Ngurah Arya; Gede Dwidasmara, Ida Bagus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
Padmasana and Pelinggih are sacred structures that hold significant importance in the religious and cultural practices of the Balinese Hindu community. Padmasana refers to the elevated throne or shrine dedicated to the highest deity in Hinduism, while Pelinggih represents small sanctuaries or shrines found in various locations. Padmasana, often located in the innermost sanctum of temples or in open spaces, symbolizes the presence of the Supreme God in Hindu belief. It is characterized by an elevated platform adorned with intricate carvings and decorations, usually in the form of a lotus or a throne-like structure. Padmasana serves as a focal point for prayers, offerings, and rituals, where devotees seek spiritual connection and guidance from the divine. Through the ontological modeling of Padmasana and Pelinggih, this research contributes to the preservation and dissemination of the cultural heritage of the Balinese Hindu community. The ontological model serves as a knowledge repository, capturing the intricate details and interrelationships of these sacred structures, fostering a deeper understanding of their spiritual significance. Ultimately, this research promotes cross-cultural understanding and encourages the preservation and appreciation of Balinese Hindu traditions.